Historicity of the National Santri Day - Miranti Rohmanda; Manneke Budiman (Faculty of Humanities, Universitas Jenderal Soedirman, 2025)
This article discusses the establishment of National Santri Day, which was created through Presidential Decree No. 22 of 2015. The date refers to the event of the Jihad Resolution declared by Kiai across Java and Madura in 1945, under the influence of President Soekarno, to assist the Indonesian people in their struggle for independence. Seventy years later, the value of the Jihad Resolution was revisited and institutionalized into the tradition of National Santri Day. The legalization of National Santri Day raises an important question regarding its timing. This research employs a qualitative method by analyzing texts related to the historicity of National Santri Day to examine the background and underlying factors behind the establishment of National Santri Day, with an emphasis on its residual, emergent, and dominant cultural aspects. The findings of this study reveal that the values of struggle and the collective trauma toward radicalism in Indonesia are utilized as residual elements preserved by the dominant authority as a means of legitimizing its power during the new governmental period in 2014.